Analisis Kekayaan Media Pada Website Dinas Kebudayaan Provinsi Sumatera Barat - Putri Rahmania; Rahmi Surya Dewi; Yessi Ratna Sari; Sarmiati Sarmiati (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2023)
The West Sumatra Provincial Culture Office is a local government in charge of cultural affairs which utilizes the website to provide information on West Sumatra culture, especially Minangkabau. This study aims to look at media richness in using websites as a means of providing information about culture in West Sumatra Province using the Media Wealth Theory by Daft and Lengel. There are four categories of media riches, namely reciprocal congruence, signal diversity, personal sources, and language diversity. The method used is descriptive qualitative with data collection carried out by observation, interviews and documentation. In this study the use of the website as a means of information by The Department of Culture of West Sumatra Province is grouped into the category of media wealth. The results of the research show that the website of The Department of Culture of West Sumatra Province was not perfect in using media riches from the four categories, and obstacles were found in website management due to minimal human resources.